Digestate biochar effects on soil Pb bioaccessibility, crop Pb concentrations, and human health risk in urban vegetable agroecosystems - Jennifer Newell; Rory Doherty; Gary Lyons; Siobhan F. Cox (Environmental Geochemistry and Health, 2026)

Microbial fuel cells to monitor natural attenuation around groundwater plumes - Panagiotis Kirmizakis; Mark Cunningham; Deepak Kumaresan; Rory Doherty (Environmental Science and Pollution Research, 2025)
This research presents a straightforward and economically efficient design for a microbial fuel cell (MFC) that can be conveniently integrated into a borehole to monitor natural attenuation in groundwater. The design employs conventional, transparent, and reusable PVC bailers with graphite tape and granular activated carbon to create high surface area electrodes. These electrodes are connected across redox environments in nested boreholes through a wire and variable resistor setup. The amended electrodes were installed in pre-existing boreholes surrounding a groundwater plume near a former gasworks facility. Among all the MFC locations tested, the MFC at the plume fringe exhibited the highest electrical response and displayed significant variations in the differential abundance of key bacterial and archaeal taxa between the anode and cathode electrodes. The other MFC configurations in the plume center and uncontaminated groundwater showed little to no electrical response, suggesting minimal microbial activity. This straightforward approach enables informed decision-making regarding effectively monitoring, enhancing, or designing degradation strategies for groundwater plumes. It offers a valuable tool for understanding and managing contaminant degradation in such environments.

Thermochemical characterisation of hydrochar from agricultural waste and its efficiency as a supplement with solid fuel - Sadish Oumabady; Satish K. Bhardwaj; Sangeetha Piriya Ramasamy; Shamsudeen U. Dandare; Ruben Sakrabani; Rory Doherty; Sree Nanukuttan; Deepak Kumaresan (Biomass and Bioenergy, 2024)

Chronic kidney disease of unknown origin is associated with environmental urbanisation in Belfast, UK - Jennifer M. McKinley; Ute Mueller; Peter M. Atkinson; Ulrich Ofterdinger; Siobhan F. Cox; Rory Doherty; Damian Fogarty; J. J. Egozcue; V. Pawlowsky-Glahn (Environmental Geochemistry and Health, 2021)
Chronic kidney disease (CKD), a collective term for many causes of progressive renal failure, is increasing worldwide due to ageing, obesity and diabetes. However, these factors cannot explain the many environmental clusters of renal disease that are known to occur globally. This study uses data from the UK Renal Registry (UKRR) including CKD of uncertain aetiology (CKDu) to investigate environmental factors in Belfast, UK. Urbanisation has been reported to have an increasing impact on soils. Using an urban soil geochemistry database of elemental concentrations of potentially toxic elements (PTEs), we investigated the association of the standardised incidence rates (SIRs) of both CKD and CKD of uncertain aetiology (CKDu) with environmental factors (PTEs), controlling for social deprivation. A compositional data analysis approach was used through balances (a special class of log contrasts) to identify elemental balances associated with CKDu. A statistically significant relationship was observed between CKD with the social deprivation measures of employment, income and education (significance levels of 0.001, 0.01 and 0.001, respectively), which have been used as a proxy for socio-economic factors such as smoking. Using three alternative regression methods (linear, generalised linear and Tweedie models), the elemental balances of Cr/Ni and As/Mo were found to produce the largest correlation with CKDu. Geogenic and atmospheric pollution deposition, traffic and brake wear emissions have been cited as sources for these PTEs which have been linked to kidney damage. This research, thus, sheds light on the increasing global burden of CKD and, in particular, the environmental and anthropogenic factors that may be linked to CKDu, particularly environmental PTEs linked to urbanisation.

Enhancement of gasworks groundwater remediation by coupling a bio-electrochemical and activated carbon system - Panagiotis Kirmizakis; Rory Doherty; Carlos A. Mendonça; Ricardo Costeira; Chris C. R. Allen; Ulrich S. Ofterdinger; Leonid Kulakov (Environmental Science and Pollution Research, 2019)

The environmental fate of polybrominated diphenyl ethers (PBDEs) in western Taiwan and coastal waters: evaluation with a fugacity-based model - Kieran O’Driscoll; Jill Robinson; Wen-Son Chiang; Yang-Yih Chen; Ruey-Chy Kao; Rory Doherty (Environmental Science and Pollution Research, 2016)

When are total concentrations not total? Factors affecting geochemical analytical techniques for measuring element concentrations in soil - Rebekka McIlwaine; Siobhan F. Cox; Rory Doherty (Environmental Science and Pollution Research, 2015)

Comparison of methods used to calculate typical threshold values for potentially toxic elements in soil - Rebekka McIlwaine; Siobhan F. Cox; Rory Doherty; Sherry Palmer; Ulrich Ofterdinger; Jennifer M. McKinley (Environmental Geochemistry and Health, 2014)

Factors affecting Sciomyzidae (Diptera) across a transect at Skealoghan Turlough (Co. Mayo, Ireland) - Christopher D. Williams; James Moran; Owen Doherty; Rory J. Mc Donnell; Michael J. Gormally; Lloyd V. Knutson; Jean-Claude Vala (Aquatic Ecology, 2009)